Implementation of Ice Breaking Strategis in Increasing Student Learning Motivation in Islamic Religius Education - Ismi Maisyaroh; Zakiyah BZ (At-tadzkir: Islamic Education Journal, 2026)
This research is motivated by students’ low learning motivation in Islamic Religious Education (PAI) subjects, characterized by a lack of concentration, participation, and Classroom interaction. One of the main causes is the use of monotonous learning methods, such as lecturing, which can lead to boredom and decrease learning enthusiasm. Therefore, this study aims to examine the implementation of ice-breaking strategies to increase student motivation for PAI learning. This research uses a qualitative approach with a case study design. The research subjects were 25 female students at the Zainul Bahar Language Institute in Bondowoso. Data collection techniques included observation, interviews, and documentation. The obtained data were analyzed through data reduction, data display, and verification to yield valid, in-depth findings. The results showed that applying ice-breaking strategies, such as educational games, mufrodat (vocabulary) games, and other interactive activities, increased students’ motivation to learn. This improvement was evident in increased student participation in learning, greater courage in expressing opinions, and heightened enthusiasm for learning activities. The implications of this study suggest that ice-breaking strategies can serve as an innovative alternative in PAI learning to create a more enjoyable, interactive, and conducive learning environment. Furthermore, the results of this study provide practical contributions for teachers in designing more creative and contextual learning and serve as a reference for the development of activity-based learning strategies in Islamic boarding school (pesantren) environments.